An algebra problem by A Former Brilliant Member

Algebra Level 2

If x 1 x = 1 x-\dfrac{1}{x}=1 , find the value of x 3 1 x 3 x^3-\dfrac{1}{x^3} .


The answer is 4.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Chew-Seong Cheong
May 16, 2017

( x 1 x ) 3 = x 3 3 x + 3 x 1 x 3 1 3 = x 3 1 x 3 3 ( x 1 x ) 1 3 = x 3 1 x 3 3 ( 1 ) x 3 1 x 3 = 4 \begin{aligned} \left(x - \frac 1x \right)^3 & = x^3 - 3x + \frac 3x - \frac 1{x^3} \\ 1^3 & = x^3 - \frac 1{x^3} - 3 \left(x - \frac 1x \right) \\ 1^3 & = x^3 - \frac 1{x^3} - 3(1) \\ \implies x^3 - \frac 1{x^3} & = \boxed{4} \end{aligned}

x 1 x = 1 x-\dfrac{1}{x}=1

( x 1 x ) 3 = 1 3 \left(x-\dfrac{1}{x}\right)^3=1^3

x 3 + 3 x 2 ( 1 x ) + 3 x ( 1 x ) 2 + ( 1 x ) 3 = 1 x^3+3x^2\left(-\dfrac{1}{x}\right)+3x\left(-\dfrac{1}{x}\right)^2+\left(-\dfrac{1}{x}\right)^3=1

x 3 3 x 2 x + 3 x x 2 1 x 3 = 1 x^3-\dfrac{3x^2}{x}+\dfrac{3x}{x^2}-\dfrac{1}{x^3}=1

x 3 3 x + 3 x 1 x 3 = 1 x^3-3x+\dfrac{3}{x}-\dfrac{1}{x^3}=1

x 3 3 ( x 1 x ) 1 x 3 = 1 x^3-3\left(x-\dfrac{1}{x}\right)-\dfrac{1}{x^3}=1 but: x 1 x = 1 x-\dfrac{1}{x}=1

x 3 3 ( 1 ) 1 x 3 = 1 x^3-3(1)-\dfrac{1}{x^3}=1

x 3 1 x 3 = 1 + 3 x^3-\dfrac{1}{x^3}=1+3

x 3 1 x 3 = 4 x^3-\dfrac{1}{x^3}=4

Or you could make it simpler by using the identity a^3 - b^3=(a - b)(a^2 + ab + b^2)

Sathvik Acharya - 4 years ago

Log in to reply

Exactly. Here a-b=1, a^2+b^2=3 and ab=1 so, a^3-b^3=1.4=4

Rajdeep Ghosh - 4 years ago

That's exactly what I used above:

x 1 x = 1 ( x ) 3 ( 1 x ) 3 = ( x 1 x ) ( x 2 + 1 + 1 x 2 ) = x - \dfrac{1}{x} = 1 \implies (x)^3 - (\dfrac{1}{x})^3 = (x - \dfrac{1}{x}) (x^2 + 1 + \dfrac{1}{x^2}) =

x 2 + 1 x 2 + 1 x^2 + \dfrac{1}{x^2} + 1

x 1 x = 1 1 = ( x 1 x ) 2 = x 2 2 + 1 x 2 x - \dfrac{1}{x} = 1 \implies 1 = (x - \dfrac{1}{x})^2 = x^2 - 2 + \dfrac{1}{x^2}

x 2 + 1 x 2 = 3 \implies x^2 + \dfrac{1}{x^2} = 3

x 3 1 x 3 = 4 \implies x^3 - \dfrac{1}{x^3} = \boxed{4} .

Rocco Dalto - 4 years ago
Munem Shahriar
Jul 7, 2017

Given that,

  • x x - 1 x \dfrac{1}{x} = 1 = 1

Now,

x 3 x^3 - 1 x 3 \dfrac{1}{x^3}

= ( x ) 3 = (x)^3 - ( 1 x ) 3 (\dfrac{1}{x})^3

= ( x = (x - 1 x ) 3 \dfrac{1}{x})^3 + + 3 3 \cdot x x 1 x \dfrac{1}{x} ( x (x - 1 x ) \dfrac{1}{x})

= ( 1 ) 3 + 3 × 1 = (1)^3 + 3 \times 1 ;[ x x 1 x \dfrac{1}{x} cancelled]

Therefore , x 3 x^3 - 1 x 3 \dfrac{1}{x^3} = 4 = 4

Rocco Dalto
May 30, 2017

x 1 x = 1 ( x ) 3 ( 1 x ) 3 = ( x 1 x ) ( x 2 + 1 + 1 x 2 ) = x 2 + 1 x 2 + 1 x - \dfrac{1}{x} = 1 \implies (x)^3 - (\dfrac{1}{x})^3 = (x - \dfrac{1}{x}) (x^2 + 1 + \dfrac{1}{x^2}) = x^2 + \dfrac{1}{x^2} + 1

x 1 x = 1 1 = ( x 1 x ) 2 = x 2 2 + 1 x 2 x 2 + 1 x 2 = 3 x - \dfrac{1}{x} = 1 \implies 1 = (x - \dfrac{1}{x})^2 = x^2 - 2 + \dfrac{1}{x^2} \implies x^2 + \dfrac{1}{x^2} = 3

x 3 1 x 3 = 4 \implies x^3 - \dfrac{1}{x^3} = \boxed{4} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...